Engineering current density in excess of 200 A mm−2 at 20 T in CORC® magnet cables containing RE-Ba2Cu3O7−δ tapes with 38 μm thick substrates. (23rd October 2015) - van der Laan, D C; Goodrich, L F; Noyes, P; Trociewitz, U P; Godeke, A; Abraimov, D; Francis, A; Larbalestier, D C
Abstract: Conductor on round core (CORC ® ) cables wound from RE-Ba2 Cu3 O7− δ coated conductors are currently being developed for the next generation of accelerator magnets because of their high flexibility and potential for high engineering current densities J E . CORC ® cables previously reached J E of 114 A mm −2 at 4.2 K and 20 T in a 7.5 mm diameter cable. Accelerator magnets require a current density of at least 300 A mm −2 and a cable-bending diameter as small as 40 mm, which has so far not been possible with superconducting tapes made on 50 μ m thick substrates. CORC ® cables made from thinner substrates could have significantly increased J E with greater flexibility as we here demonstrate with a CORC ® cable made of tapes with 38 μ m thick substrates. A custom cable machine produced higher cable quality and better retention of tape performance compared to previous cables that were wound by hand. The thinner substrate showed an almost twofold increase in engineering current density from 114 A mm −2 to 216.8 A mm −2 at 4.2 K and 20 T, at a reduction in cable diameter from 7.5 mm to 6.0 mm. The results clearly demonstrate that winding CORC ® cables from tapes with thinner substrates is a straightforward method for raising their current density and one that shows great promise for use in accelerator magnets.